A correlation of metallic surface roughness with its hydrophobicity for dropwise condensation. (2020) - Baghel, Vishakha; Sikarwar, Basant Singh; Sharma, Deepak Kumar; Avasthi, D.K.
Abstract: The surface morphology alike lotus leaf has high contact angle and low contact angle hysteresis with respect to water droplet because of nanoscale roughness superimposed on micro order roughness in well-organized manner. The major application of superhydrophobic metallic substrate is in the condensing unit of energy and water harvesting devices. In this work, nanoscale roughness is superimposed on micro-order roughness of Aluminum substrate. The chemical texturing method is used to create micro-scale roughness onto Al surface. However, 0.6 keV Ar ions are irradiated for various time span to fabricate nano order roughness on chemically etched substrate. The roughness of samples is measured by Atomic Force Microscopy and static contact angles and their hysteresis are measured by lab customize Goniometer. It is found that the static contact angle and contact angle hysteresis increases after irradiation on chemical etched surfaces. Multi-scale roughness is observed on irradiated substrate. Results also shows that contact angle increases with increasing time of irradiation. However, maximum change in static contact angle is observed for samples irradiated for 45 s. Eventually, the static contact angle is correlated with its surface roughness. This correlation is vital for optimizing parameter affecting condensation rate in dropwise condensation. Finally, the moist air condensation experiments are conducted to know the condensation efficacy of the irradiated substrate. Also, it is found that the drop sliding frequency on vertical irradiated Al substrate is higher than the chemical etched Al substrate.